METODE PENDIDIKAN AGAMA HINDU DALAM AJARAN TRI KAYA PARISUDHA DENGAN MENGGUNAKAN APLIKASI YOUTUBE DI ERA REVOLUSI INDUSTRI 4.0 - Yudhi Dharmawan, Ida Bagus Ngurah (JAPAM (Jurnal Pendidikan Agama), 2024)
This article was compiled for the use of YouTube as a learning medium for Hindu religious education based on the teachings of Tri Kaya Parisuda in the industrial revolution era. Hindu Religious Education follows the principles of 2013 Curriculum learning, which encourages students to carry out scientific approach-based learning with the idea of ​​personality education. Leads to character education. in this case the learning of Hindu Religious Education is based on the teachings of Tri Kaya Parisuda. The scientific approach was transformed into a learning model centered on student learning and the teacher as a facilitator and motivator. In the era of the industrial revolution 4.0, the millennial generation is expected to be able to answer the challenges of this era, by utilizing social media, namely YouTube as a learning medium for Hindu Religious Education. Because currently the youtube application is in great demand and how to use it is easy, quick to get information, and information can be used and can be accessed by the wider community, videos can be used for a long time, and youtube is expected to help students receive information easily and accurately.